Hubungan profil lipid dan C-reactive protein (CRP) dengan derajat stenosis koroner pada penyakit jantung koroner stabil - Katarina Noviyanti; Edward Kurnia Setiawan L (DiscoverSys Inc., 2019)
Background: Inflammation and dyslipidemia play an important role in the formation of atherosclerotic plaques in stable coronary artery disease (SCAD). The stenosis degree indicates a visual evaluation of the percentage reduction of coronary diameter compare to normal coronary. This study aims to determine the correlation of lipid profiles, CRP with the stenosis degree in SCAD.Methods: Cross sectional study was carried in 31 patients with SCAD who had coronary angiography at Dr. Kariadi. The study used secondary data from February - March 2018 at Dr. Kariadi Semarang. Secondary data included levels of total cholesterol, LDL, HDL, triglycerides and CRP. The stenosis degree was obtained from coronary angiography in percentage units. Statistical analysis used Spearman Correlation test, p < 0,05 was considered significant.Result: Median (min-max) levels of total cholesterol, HDL, LDL, triglycerides, CRP and stenosis degrees respectively are 156 (104-283), 41 (13-67), 102 (60-190), 116 (60- 216), 1.50 (0.50-6.54), 70 (20-100). Correlation of total cholesterol, HDL, LDL, triglycerides and CRP levels with a degree of coronary stenosis are (r = 0.123; p = 0.511), (r = -0.132; p = 0.479), (r = 0.073; p = 0.697), (r = 0.117; p = 0.531), (r = 0.026; p = 0.891).Conclusion: There are no significant correlation between lipid profiles, CRP with stenosis degree in SCAD. The effect of statin drugs has an effect on dyslipidemia and as an anti-inflammatory.